Strategic Integration of Information Technology in Human Resource Management: a Pathway to Industry 4.0 and Society 5.0 Synergy - Maulana, Bobby Akbar; Yunus, Muhammad; Fakhriyah, Siti Elfa; Khuzaini, Khuzaini; Shaddiq, Syahrial (PT. Hanken SUkses Jaya, 2024)
The strategic integration of Information Technology (IT) in Human Resource Management (HRM) is pivotal in navigating the transformative landscapes of Industry 4.0 and Society 5.0. This study explores the intricate connections between IT and HRM, emphasizing the synergistic pathway forged amidst the convergence of smart technologies and human-centric solutions. Insights from seminal works such as